Utilization of organs from donors after circulatory death for vascularized pancreas and islet of Langerhans transplantation: recommendations from an expert group. (24th September 2015) - Berney, Thierry; Boffa, Catherine; Augustine, Titus; Badet, Lionel; de Koning, Eelco; Pratschke, Johann; Socci, Carlo; Friend, Peter
Summary: Donation after circulatory death (DCD) donors are increasingly being used as a source of pancreas allografts for vascularized organ and islet transplantation. We provide practice guidelines aiming to increase DCD pancreas utilization. We review risk assessment and donor selection criteria. We report suggested factors in donor and recipient clinical management and provide an overview of the activities and outcomes of vascularized pancreas and islet transplantation.